Prescribing diatom morphology: toward genetic engineering of biological nanomaterials - Kroeger, N (Current opinion in chemical biology, 2007)
The formation of inorganic materials with complex form is a widespread biological phenomenon (biomineralization). Among the most spectacular examples of biomineralization is the production by diatoms (a group of eukaryotic microalgae) of intricately nanopatterned to micropatterned cell walls made of silica (SiO 2). Understanding the molecular mechanisms of diatom silica biomineralization is not only a fundamental biological problem, but also of great interest in materials engineering, as the biological self-assembly of three-dimensional (3D) inorganic nanomaterials has no man-made analog. Recently, insight into the molecular mechanism of diatom silica formation has been obtained by structural and functional analysis of biomolecules that are involved in this process. Furthermore, the rapid development of diatom molecular genetics has provided new tools for investigating the silica forming machinery of diatoms and for manipulating silica biogenesis. This has opened the door for the production, through genetic engineering, of unique 3D nanomaterials with designed structures and functionalities.